The Sensitivity Pattern of Bacteria Against Antibiotics in Urinary Tract Infection Patients at RSD DR. Soebandi Jember - Ryan Ravi Is Syahputra; Dini Agustina; Septa Surya Wahyudi (Journal of Agromedicine and Medical Sciences, 2018)
Urinary tract infection (UTI) was infection by microorganisms in the urinary tract. Treatment of UTI required supportive therapy and adequate antibiotics. Antibiotic resistance was the solution in the treatment of UTI, so it is important to assess the factors of bacterial resistance and strategies to control the incidence of resistance by choosing antibiotics in accordance with the pattern of sensitivity of germs obtained. This study aimed to determine the pattern of bacterial susceptibility to antibiotics in patients with UTI in RSD dr. Soebandi Jember. This research used descriptive research design by taking secondary data that was medical record data of urine culture examination and sensitivity test to antibiotics in UTI patients who have been diagnosed in inpatient and outpatient room RSD dr. Soebandi Jember between the period January 1, 2014 until November 30, 2017. The results of this study obtained 57 samples of urine positive bacteria, which found 18 types of bacteria that caused UTI. Of the 18 types of bacteria, there were 16 Gram negative bacteria and 2 Gram positive bacteria. Five bacteria divided among others E. coli on 24 samples, K. ornithinolytica on 5 samples, K. pneumoniae on 4 samples, B. cepacia on 4 samples, and E. cloacae on 3 samples. The results of bacterial sensitivity to antibiotic pattern showed the highest sensitivity level ie amikacin, fosfomicin, netilmicin, gentamicin, and nitrofurantoin. While the results of patterns of bacterial resistance to antibiotics based on hormonal levels of cephalotin, cephazolin, ampicillin, sulphametoxazole, and trimetoprim. Keywords: Urinary Tract Infection (UTI), Bacterial sensitivity, Antibiotics